Anti-Doping - Jelkmann W (Deutsche Zeitschrift für Sportmedizin)
Experimental evidence suggests that xenon (Xe) is not completely inert but can affect the functional properties of proteins, particularly that of ion channels and of enzymes. According to recent reports xenon can activate the hypoxia-inducible transcription factors (HIF). A number of preclinical investigations (cell culture experiments, animal studies) has been performed concerning this, but the results have been volatile and the mechanism of HIF activation differed from that of hypoxia. Exposure to xenon (generally at 70 vol%) increased HIF-1 mRNA and HIF-1 protein levels in some studies, while in others, the HIF-2 mRNA and HIF-2 protein levels were increased instead. There is one single study in mice where increased renal levels of the HIF target proteins erythropoietin (EPO) and vascular endothelial growth factor (VEGF) were detected on Western blots at 24 h after xenon exposure of the animals. Effects of xenon treatment on the blood level of EPO have never been reported. No human data are available with respect to the HIF system and the production of EPO. Still, for reasons of precaution xenon has been included as HIF activator in WADAs Prohibited List 2014. However, compared to the numerous chemical substances that increase HIF-dependent EPO synthesis in humans, the author considers the potential misuse of xenon in sports a minor issue.Key Words: Blood doping, erythropoietin, gene expression, hypoxia, oxygen transport